Baltic Fucus vesiculosus as potential bio-sorbent for Zn removal: Mechanism insight. (January 2020) - Brinza, Loredana; Geraki, Kalotina; Cojocaru, Corneliu; Holdt, Susan Løvstad; Neamtu, Mariana
Abstract: This research aimed to find the best phenotype of the brown algae Fucus vesiculosus (kelp) which has the greater potential to become a sorption byproduct for Zn removal from contaminated waters. Thus, the Zn uptake capacity and sorption mechanisms of the kelp collected from the Baltic Sea shore was, for the first time, investigated under various conditions, and compared to the phenotype habiting on the Irish Sea shore. Sorption studies were performed investigating the effect of algal dosage, Zn sources as well as algal harvesting time of the year on Zn uptake capacity. The results suggested that the Baltic algae is a better bio-sorbent for Zn uptake. Sorption mechanisms were studied by employing various indirect and direct approaches, more importantly, including high resolution synchrotron X-Ray Fluorescence and X-Ray Absorption Spectroscopy (XAS) and molecular modelling (MM). The results revealed that alginate and cellulose are among the main polysaccharide bonding Zn at algal surface, via coordination with O atoms from carboxyl and hydroxyl groups. XAS results giving direct measurements of Zn bonding environment on algal surface are supported by MM outputs and suggested that Zn is surrounded by ca. 5 O atoms at interatomic distances varying from 1.94 to 2.02 Å. The results contribute to understanding sorption mechanisms which can further lead to finding the best eluent for Zn desorption from the used biomass, bio sorbent reconditioning and reuse in multiple sorption desorption cycles as well as process optimization before industrial scaling up. Graphical abstract: Image 1 Highlights: The Baltic kelp has better sorption capacity compared to the Irish kelp. Indirect investigations suggests that ion exchange is one of Zn sorption mechanism. Direct investigations of Zn uptake showed that Zn is bond by alginate and cellulose. Synchrotron XAS showed that Zn is bond by 5 O atoms at distances of 1.97–2.03 Å. Molecular modelling revealed that Coulomb interactions were involved in Zn binding.